2017
DOI: 10.1016/bs.acdb.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Mental Objects in Working Memory

Abstract: Working memory is the small amount of information that we hold in mind and use to carry out cognitive processes such as language comprehension and production, problem-solving, and decision-making. In order to understand cognitive development, it would be helpful to know whether working memory increases in capacity with development and, if so, how and why. I will focus on two major stumbling blocks toward understanding working memory development, namely that (1) many potentially relevant aspects of the mind cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Manrique et al humans (aged 25 to 80) showed associations between white-matter-WM over multiple white-matter tracts, which reinforces the idea of WM being a widely distributed resource (Christophel et al, 2017), one requiring dynamic agile communication across multiple brain regions. Cowan (2017) suggests that measuring working memory during child development from infancy through childhood is complicated by two aspects of working memory that develop differently. One is the number of files that provide the storage location for the information inserted into temporary memory.…”
Section: Relation Between Growth In White Matter and Expansion Of Ewmsmentioning
confidence: 99%
“…Manrique et al humans (aged 25 to 80) showed associations between white-matter-WM over multiple white-matter tracts, which reinforces the idea of WM being a widely distributed resource (Christophel et al, 2017), one requiring dynamic agile communication across multiple brain regions. Cowan (2017) suggests that measuring working memory during child development from infancy through childhood is complicated by two aspects of working memory that develop differently. One is the number of files that provide the storage location for the information inserted into temporary memory.…”
Section: Relation Between Growth In White Matter and Expansion Of Ewmsmentioning
confidence: 99%
“…Previous studies have mainly focused on the simple task of recall, which entails temporary maintenance of information in WM (see also Cowan, 2017). Here, we focused instead on the interaction between LTM and updating, a complex WM function that comprises not only temporary maintenance of information but also item substitution (see Ecker et al, 2010).…”
Section: The Current Studymentioning
confidence: 99%
“…This categorization allows generalization across various sensory inputs that require the same behavioral response 6,7 , which is essential in our detailed and sensory rich environment 8,9 . However, grouping of information to reduce WM content also introduces additional sensory biases and inevitably reduces the precision of memory representations 10,11 (e.g., leading to a confusion of umbrellas differing only in their exact shade of blue).…”
mentioning
confidence: 99%